Psychometric validation of the Thai version of the 12-item Zarit Burden Interview among informal caregivers in a palliative care setting in the south of Thailand. - Ueamporn Summart; Thanaporn Kaewbubpha; Ornicha Saengnil; Prasertsri Kongkaur; Suparuek Mahorasop; Suchittra Saengkhum; Yuwadee Wittayapun (PLoS ONE)
The Thai version of the 12-item Zarit Burden Interview (ZBI) is valid for measuring caregiver burden in psychiatric caregivers. Nevertheless, it has not been verified in a larger palliative care (PC) context. The aim of this study was to validate the 12-item ZBI in PC among caregivers of palliative care patients. A methodological study examining the validity of the 12-item ZBI was carried out with informal caregivers of palliative care patients of two district health service networks. The data were gathered using self-administered questionaries, and then all participants were randomly split into two sub-samples for exploratory factor analysis (EFA) (n = 150) and confirmatory factor analysis (CFA) (n = 155). After utilizing statistical approaches for reducing items, EFA was used with group 1 to analyze the factor structure of the 12-item ZBI. Finally, CFA was employed with group 2 to confirm the amended structure indicated by the EFA and to evaluate the construct validity of the 12-item ZBI. A total of 305 palliative caregivers were enrolled. The principal component analysis of the 12 items yielded a loading based on a two-factor model of personal strain and role strain accounting for 61.4% of the variance. Cronbach's alpha (0.83) and item-total correlations (rho = 0.38-0.70) showed that the 12-item Zarit had acceptable reliability. For convergent validity, the average variance extracted (AVE) values revealed that all 12-item ZBI subscales had a convergence effect, with AVEs ranging from 0.50-0.53. Additionally, this tool had a significant positive correlation with depressive symptoms (r = 0.48), anxiety (r = 0.38), and stress (r = 0.56). The 12-item ZBI is a brief, precise, and valid instrument for assessing burden among Thai palliative caregivers. We discovered high evidence of reliability in this sample, along with convergent and construct validity. Likewise, EFA revealed that the 12-item ZBI was a two-dimensional scale. Thus, health care practitioners may utilize the ZBI in research and clinical settings to determine burden in palliative caregivers.